Use of Electronic Information Sources by the Faculty Members of Social Science Departments in Annamalai University: A Study - Nagarajan, M (International Journal of Computer Sciences and Engineering, 2019)
This paper aim at analyzing use of electronic resources by the Faculty members of Social Science departments, Annamalai University. From this study the investigator is able to find out that most the Faculty members prepare Wikipedia as the first source of information for guiding the students. This study reveals that the majority of the Faculty members are using e-resources more than one hour.